Adaptation to high altitude hypoxia protects the rat heart against ischemia-induced arrhythmias. Involvement of mitochondrial K(ATP) channel - Asemu, G; Papousek, F; Ostádal, B; Kolár, F (Journal of molecular and cellular cardiology, 1999)
The aim was to determine whether adaptation to chronic hypoxia protects the heart against ischemic arrhythmias and whether ATP-dependent potassium channels (K(ATP)) play a role in the antiarrhythmic mechanism. Adult male rats were adapted to intermittent high altitude hypoxia (5000 m, 4 h/day) and susceptibility to ischemia-induced ventricular arrhythmias was evaluated in the Langendorff-perfused hearts subjected to either an occlusion of the coronary artery for 30 min or pre-conditioning by brief occlusion of the same artery prior to 30-min reocclusion. In separate groups, either a K(ATP) blocker, glibenclamide (10 micromol/l), or a mitochondrial K(ATP) opener, diazoxide (50 micromol/l), were added to a perfusion medium 20 min before the occlusion. Adaptation to hypoxia reduced the total number of ventricular arrhythmias by 64% as compared with normoxic controls. Preconditioning by a single 3-min coronary artery occlusion was antiarrhythmic only in the normoxic group, while two occlusion periods of 5 min each were needed to pre-condition the hypoxic hearts. Glibenclamide increased the number of arrhythmias in the normoxic hearts from 1316+/-215 to 2091+/-187 (by 59%) and in the hypoxic group from 636+/-103 to 1777+/-186 (by 179%). In contrast, diazoxide decreased the number of arrhythmias only in the normoxic group from 1374+/-96 to 582+/-149 (by 58%), while its effect in the hypoxic group was not significant. It is concluded that long-term adaptation of rats to high altitude hypoxia decreases the susceptibility of their hearts to ischemic arrhythmias and increases an antiarrhythmic threshold of pre-conditioning. The mitochondrial K(ATP) channel, rather than the sarcolemmal K(ATP) channel, appears to be involved in the protective mechanism afforded by adaptation.
Keywords: srdeční mitochondrie; membránové proteiny; Rats; hypoxie; Hypoxia; Membrane Proteins; iontové kanály; srdeční arytmie; aklimatizace; Glyburide; mužské pohlaví; Rats, Wistar; Myocardial Ischemia; srdeční komory; Arrhythmias, Cardiac; Acclimatization; Heart Rate; krysa rodu Rattus; Mitochondria, Heart; srdeční frekvence; zvířata; Altitude; glibenklamid; Potassium Channels; Heart Ventricles; draslíkové kanály; Heart; ischemická choroba srdeční; Ion Channels; nadmořská výška; potkani Wistar; srdce; Male; Animals